Impact Of The Use Of Interactive Multimedia-Based Teaching Material On The Motivation To Learn Heat Matter And The Transfer Of High Matter In Study Class V SD Inpres Tello Baru 1.1 - Nurazizah, Reski; Nurhaedah, Nurhaedah; Sayidiman, Sayidiman (Program Studi PGSD FIP UNM, 2024)
This research was conducted on the basis of problems found at SD Inpres Tello Baru 1.1, namely low student learning motivation. This research aims to determine the effect of using interactive multimedia-based teaching materials on the motivation to learn summer science material and the progress of fifth grade elementary school students Tello Baru 1.1. This research is included in experimental research with quantitative approach. The independent variable in this research is open material based on interactive multimedia, while the dependent variable is learning motivation. The population in this study were all fifth grade students at SD Inpres Tello Baru 1.1 with a total of 38 people, while the sample was the VA class as a class experiment with 19 students and class VB as the control class with 19 people as comparison. Research data obtained with learning motivation questionnaires in the form of pre-nontest and post-nontest. Analysis of results Descriptive shows the use of open edugame materials goes by category low at pre-nontest and high post-nontest. Results of inferential analysis with using the independent sample t test shows that there are differences in results post-nontest between the experimental and control classes which means there is motivation learning science in the experimental class was better than in the control class. So that it can be concluded that interactive multimedia-based teaching materials are influential with > 0.05 in increasing motivation to learn science and hot material movement of class V students at SD Inpres Tello Baru 1.1.